Investigation of optimum N-terminal probrain natriuretic peptide level in patients on maintained hemodialysis - Chen, Lan (Ren Fail, 2017)
Background: Serum N-terminal probrain natriuretic peptide (NT-proBNP) level is known to be strongly associated with fluid overload, and serves as a guide for fluid management in patients on hemodialysis (HD). This study aimed at investigating the relationship between NT-proBNP level and blood pressure (BP), ultrafiltration/dry weight ratio as well as hemoglobin, and to explore the optimal cutoff point of NT-proBNP level in Chinese patients on HD. Methods: A total of 306 patients on maintained HD for stage 5 chronic kidney disease (CKD) were included in this prospective study. Their average ultrafiltration/dry weight ratio and BP before dialysis were recorded. The serum NT-proBNP, hemoglobin, serum calcium, and phosphorus were detected. The cutoff value for NT-proBNP level was calculated using receiver operating characteristic (ROC) analysis. Results: The high NT-proBNP level was associated with high BP and ultrafiltration/dry weight ratio, and low hemoglobin level. The optimal cutoff point of NT-proBNP level for patients on maintained HD was 5666 pg/mL, with a sensitivity of 78.5%, specificity of 43.9%, and area under the curve (AUC) of 0.703 (<0.001). Conclusions: NT-proBNP level ≤5666 pg/mL was recommended to achieve the target BP, hemoglobin level, and ultrafiltration/dry weight ratio in patients on maintained HD with an ejection fraction (EF) >50%.